2017
DOI: 10.1155/2017/4076348
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Mitochondrial Disorders in Septic Cardiomyopathy

Abstract: Sepsis is defined as a life-threatening organ dysfunction caused by a dysregulated host response to infection. It remains a leading cause of death worldwide, despite the development of various therapeutic strategies. Cardiac dysfunction, also referred to as septic cardiomyopathy, is a frequent and well-described complication of sepsis and associated with worse clinical outcomes. Recent research has increased our understanding of the role of mitochondrial dysfunction in the pathophysiology of septic cardiomyopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 116 publications
(141 reference statements)
2
45
0
Order By: Relevance
“…Evidence from our lab and others has demonstrated a major role for endotoxin lipopolysaccharides (LPS) released from Gram‐negative bacteria in the inflammatory response and cardiovascular homeostasis in sepsis (Pfalzgraff & Weindl, ; Ren et al, ; Zhang et al, ). Although antioxidants (such as metallothionein, insulin‐like growth factor I and catalase), mitochondrial protein aldehyde dehydrogenase (ALDH2) and ER chaperones have shown some promise in the treatment of septic cardiomyopathy (Ceylan‐Isik et al, ; Durand et al, ; Pang, Peng et al, ; Turdi et al, ), clinical validation has not been consolidated for antioxidants and mitochondrial drugs in sepsis and septic hearts. More recent findings from our group and others depicted a rather pivotal role for autophagy dysregulation in the onset and development of septic cardiomyopathy (Pang, Peng, et al, ; Pang, Zheng, et al, ; Piquereau et al, ; Ren et al, ; Sun et al, ), although the mechanism behind sepsis‐induced autophagy dysregulation is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from our lab and others has demonstrated a major role for endotoxin lipopolysaccharides (LPS) released from Gram‐negative bacteria in the inflammatory response and cardiovascular homeostasis in sepsis (Pfalzgraff & Weindl, ; Ren et al, ; Zhang et al, ). Although antioxidants (such as metallothionein, insulin‐like growth factor I and catalase), mitochondrial protein aldehyde dehydrogenase (ALDH2) and ER chaperones have shown some promise in the treatment of septic cardiomyopathy (Ceylan‐Isik et al, ; Durand et al, ; Pang, Peng et al, ; Turdi et al, ), clinical validation has not been consolidated for antioxidants and mitochondrial drugs in sepsis and septic hearts. More recent findings from our group and others depicted a rather pivotal role for autophagy dysregulation in the onset and development of septic cardiomyopathy (Pang, Peng, et al, ; Pang, Zheng, et al, ; Piquereau et al, ; Ren et al, ; Sun et al, ), although the mechanism behind sepsis‐induced autophagy dysregulation is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence demonstrates the causative involvement of mitochondrial dysregulation [ 4 ]. Mitochondrion is a semi-self-replicating organelle containing its own genome.…”
Section: Introductionmentioning
confidence: 99%
“…Nrf2 knockdown inhibits mitochondrial biogenesis with downregulation of PGC-1α [ 11 ], while PGC-1α potentiates Nrf2-mediated antioxidant response [ 12 ], indicative of the presence of Nrf2/PGC-1α feedback loop. Mitochondrial reactive oxygen species (ROS) is a driving force for mitochondrial dysfunction in septic cardiomyopathy [ 4 ], while PGC-1α is responsive to the alternations in cellular energetic demands and redox status [ 13 ]. Therefore, finding the role of Nrf2 in the cooperation with PGC-1α would provide important insight into the action of antioxidant defenses from the aspect of mitochondrial biogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the role of ROS is increasingly gaining attention in the chemotherapy mechanisms of tumors [49]. Studies have shown that, PTX can affect the activities of SOD and MDA in cancer cells [50], which will result in the severely imbalanced antioxidant capacity in cancer cells as well as the markedly elevated ROS level, eventually killing the cancer cells. Some recent studies have reported that various forms of Se can react with the reducing glutathione to produce ROS, which can thereby trigger some apoptotic signaling pathways and promote cancer cell apoptosis [51].…”
Section: Discussionmentioning
confidence: 99%